2017
DOI: 10.5109/1808452
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state Analysis of Supersonic Mixing Enhanced by a Three-dimensional Cavity Flow

Abstract: The supersonic mixing field induced by a novel wall-mounted cavity having a three-dimensional shape is investigated computationally. In the computation, the Reynolds-averaged Navier-Stokes (RANS) equations are solved to obtain the steady state solution. The resulting pattern of limiting streamlines is compared with the previous result of oil-flow surface visualization. The comparison shows that the pattern of limiting streamlines agrees well with the oil flow pattern not only inside the cavity but also around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…As it has been explained earlier, combustion processes nowadays require extensive study especially on how to improve its performance [79][80][81] . Recently, studies have shown that using an asymmetric vortex combustor for flameless combustion is possible.…”
Section: Asymmetric Swirling Flameless Combustionmentioning
confidence: 99%
“…As it has been explained earlier, combustion processes nowadays require extensive study especially on how to improve its performance [79][80][81] . Recently, studies have shown that using an asymmetric vortex combustor for flameless combustion is possible.…”
Section: Asymmetric Swirling Flameless Combustionmentioning
confidence: 99%
“…If the flow velocity after the mixing section exceeds the speed of the sound, a normal shock will happen in the constant area section. It starts with the conservation of mass 28) : (17) Conservation of momentum: (18) Conservation of energy:…”
Section: Normal Shockwave Inside the Constant Area Sectionmentioning
confidence: 99%
“…The same area of study about the wind turbine performance is also being numerically investigated in terms of the turbine power coefficient over the 2D hill [5]. Another utilization of CFD method is applied in the study of the novel wall-mounted cavity having a three-dimensional shape [6]. Apart from the CFD approach, a dynamic modeling had been used to simulate the transient performance of a heat pump system that is being utilized to develop the smart-controlled thermal energy system [7].…”
Section: Introductionmentioning
confidence: 99%